Review of antidiabetic activity of “Rang Jeud” Thunbergia laurifolia - Piya Kosai, Kanitta Jiraungkoorskul, Wannee Jiraungkoorskul (Journal of Applied Pharmaceutical Science, 2015)
Diabetes mellitus still is the serious medical problem to human health due to rapid increase and lead the cause of death in the developed and developing countries. It characterizes by hyperglycemia because there is the defect in insulin secretion, or the reduced sensitivity of the tissue to insulin. The clinical reports revealed that diabetes cannot be cured completely. The newer anti-hyperglycemic drugs continue searching because the existing synthetic drugs have several limitations. Traditional medicinal plants and their phytochemical substances have been used in the treatment of diabetes mellitus and associated secondary complications more than a century, but only a few of these have proofed their safe and efficacious. The aim of this review article is focused Thunbergia laurifolia one of the medicinal plants used for antioxidant activities. T. laurifolia contains several kinds of glycosides, flavonoids, gallic acid and phenolic compounds. Many researches have evaluated that these phytochemical substances have the major impact on diabetes. In conclusion this review focuses on the hypoglycemic activity of this plant and clear that it has the potential to be considered as a candidate for preparing new treatment of diabetes mellitus.
Keywords: Diabetes mellitus, herb, hypoglycemia, plant, Thunbergia laurifolia.